EDUKASI DAN PENERAPAN POLA HIDUP BERSIH DAN SEHAT (PHBS) BERBASIS SAINS DI LINGKUNGAN YAYASAN PONPES ASH-SAMADI NWDI TANAK MAIK - Fena Prayunisa; Alpi Zaidah; Ermila Mahariyanti; Irwansah Irwansah; Usman Usman; Hendri Hendri; Windi Efendy; Jufrihadi Jufrihadi; Karin Nitiasari; Fely Yuliantari (LPPM Institut Pendidikan Nusantara Global, 2025)
This community service activity aims to improve awareness, knowledge, and practices of Clean and Healthy Living Behavior (PHBS) within the Ash-Samadi NWDI Islamic Boarding School Foundation through a science-based approach. The program was motivated by the low level of hygiene behavior among students (santri) due to limited facilities and a lack of scientific understanding of the importance of cleanliness. The implementation method used an action-oriented community intervention model consisting of preparation, education, implementation, mentoring, and evaluation stages. Education was carried out through interactive training, simple scientific demonstrations, and hands-on practices such as the construction of handwashing stations, waste sorting bins, and organic composters. Data were collected through observation, in-depth interviews, and focus group discussions (FGD). The results showed a significant improvement in students’ awareness and behavior regarding personal and environmental hygiene. The students gained scientific understanding of the relationship between cleanliness and health, and an environmentally conscious student group was formed to ensure program sustainability. Thus, this activity demonstrates that a science-based approach in PHBS education is effective in shaping healthy living behaviors and can serve as a model for similar implementations in other Islamic educational institutions.